(untitled) (Research, Society and Development, 2022)
The quality classification of fruits and vegetables is used to select safety products for human consumption. Thus, this paper aims to investigate the quality classification system of the banana supply chain offered in retail and wholesale in Alto Tietê Region, Brazil. We collected 239 bananas from 12 main retail-wholesaler and applied the Banana Classification Criteria, of the Brazilian Modernization of Horticulture Program & Integrated Fruit Production. Therefore, we considered the quality criteria: gross and net weight, length, caliber, degree of maturation, and the number of defects. We observed that the banana showed a good classification with an average of gross and net weight respectively 156.49 ± 39.62 and 98.93 ± 30.11, length 21.11 ± 2.35, caliber 37.06 ± 3.08. We found an association among quality criteria and bananas classification (Dunn test, p < 0.05), as well as, among kind of defects and lots analyzed (χ² = 98.11; p < 0.05). Thirty-eight percent of the total bananas evaluated were free of defects, but 62% showed some kind of defects. In addition, considering the banana classification process we proposed a framework correct destination, such as 44% of banana should be sent to the organic fertilizer industry, 17% to the animal feed industry, 1% to the human food industry, and 38% to fresh sales in the market to human consumption. We concluded that the classification process help in the transparency of the food supply chain and the quality monitoring and control should be continuous during the fruits are exposed to sale to the consumer, guarantee the food safety, waste reduction, and correct destination of bananas that are not good for commercialization.